The Creativity Strategy on Enhancing the Cultural Brand for Xinyang City, China - Wei, Zhang; Mastika, Lamat (UNIMAS, 2025)
The research scope of this study is the City Cultural Brand of Xinyang City, China. In the global context of rapid urbanization, an increasing number of cities have recognized the pivotal role of cultural brands in distinguishing themselves and cultivating unique identities, and have begun to prioritize the development of city cultural brands, thereby enhancing city culture and expanding the international influence of these brands. As the capital of Mao Jian, a medium-sized city in central China, Xinyang is also the only city in China to be listed as one of the top ten liveable cities in China for ten consecutive years. However, the urban cultural brand of Xinyang City lacks the necessary popularity and recognition. This hinders the city from attracting tourists, investors, and facilitating cooperation that is beneficial to its economy and culture. There is an urgent need for a comprehensive innovation strategy to address the issue of the insufficient development of Xinyang City's cultural brand. This study adopts a combined qualitative and quantitative research method. Through literature collection, field investigation, observation interviews, and questionnaire design, 481 residents who have lived in Xinyang for many years will be surveyed. More than half of the respondents are those who have lived in Xinyang for over ten years. They come from various industries, ensuring a comprehensive understanding of Xinyang's city cultural brand. The study found that Xinyang has rich and diverse cultural resources. One of the most representative is tea culture. The tea-related bases and natural attractions in Xinyang (Ji Gong Mountain and Nan Wan Lake) are the most favorable. There are no particularly famous and distinctive cultural tourism products except for tea. Most people are not familiar with cultural activities except for the Tea Culture Festival, the South Bay Lake Fishing Festival, and the food festival. So, the cultural brand of Xinyang city can be positioned as the landscape tea capital, livable Xinyang. However, Xinyang City’s cultural brand is relatively unknown at home and abroad, and cultural facilities, cultural activities and cultural tourism products are scarce and lacking in creativity. By studying the cultural brand construction experience of advanced cities at home and abroad, and combining the actual situation of Xinyang city cultural brand and questionnaire survey results, Finally, the theory of integrated marketing communication is applied from the aspects of Brand communication body, content of communication, channels of communication and mode of communication propagation and communicating effect are used to establish a creative strategic framework for promoting Xinyang’s city cultural brand, to provide useful reference and guidance for the construction of city cultural brand in Xinyang and other cities at home and abroad.